Indonesia : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
The statistical data on developments in gross domestic product by sector of origin and by expenditure, agricultural production, production, domestic use, and exports of petroleum, approvals of foreign investment projects by economic sector, indices of inflation, consumer price index, summary of central government operations, and central government revenue of Indonesia are presented in the paper. The data on details of nontax receipts, Bank Indonesia liquidity support, foreign exchange and equity markets, balance of payments, and related economic indices are also presented.